Technology transfer (TT): level of absorbtive capacity and technological capabilities in mega construction projects / Roshartini Omar - Omar, Roshartini (Institute of Graduate Studies, UiTM, 2012)
The concept of ‘technology transfer’ or TT projects emerges as an important business and managerial concern for many developing countries. TT in construction is seen as an effective mechanism to increase the flow of technological development by acquiring newer technology from abroad in response to a changing economic environment. The concept of TT in construction organisations could occur simultaneously, involving the flow of imported technology (i.e., knowledge, skills and tools) via construction projects.